ANALYSIS OF FOOD SECURITY INDEX IN EAST JAVA: A SPATIAL APPROACH AND POLICY PROJECTION - Mochammad Iskandar Zulkarnain; Syarif Imam Hidayat; Noor Rizkiyah (RADJA PUBLIKA, 2025)
This study aims to analyze food security in East Java Province using a quantitative spatial approach and statistical projection. Secondary data from 2019 to 2023 were obtained from BPS (Statistics Indonesia), BKP (Food Security Agency), and the Ministry of Agriculture, covering indicators of food availability, accessibility, and utilization. The analysis was conducted using ArcGIS software for map visualization and the Single Exponential Smoothing (SES) method for projecting the Food Security Index for 2024. Spatial analysis revealed disparities in food security across regions: northern and western districts tend to be classified as